The Longitudinal Associations between Perceived Descriptive Peer Norms and Eating and Drinking Behavior: An Initial Examination in Young Adults - Jones, Andrew; Robinson, Eric (Frontiers in Psychology, 2017)
Experimental and cross-sectional studies indicate that perceptions of the eating and drinking behaviour of one’s peers (perceived descriptive peer norms) are associated with the types, frequency and quantity of food and beverages a person chooses to consume. At present we know very little about the longitudinal association between perceived descriptive peer norms and future eating or drinking behaviour. In this study we examined whether perceived descriptive peer norms for different food/ beverage types predicted frequency of consumption of food/beverages in university students. Three hundred and forty participants completed measures at baseline and follow-up for frequency of consumption of cakes/pastries, sugar containing beverages and alcoholic beverages, as well as measures of perceived descriptive peer norms at both time points. Perceived descriptive peer norms predicted consumption of pastries/cakes at follow up when controlling for changes in these perceptions over time; believing that one’s peers frequently consumed cakes/pastries was associated with an increased frequency of consumption over time, although the magnitude of this effect was small. There was no significant association between perceived descriptive peer norms and changes in frequency of consumption of sugar containing beverages or alcohol over time. In the present longitudinal study of young adults, beliefs about how often one’s peers eat or drink specific food and beverages types had limited effect on future eating and drinking behaviour.